2009
DOI: 10.1007/s00044-009-9261-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional QSAR and pharmacophore mapping of biphenyl benzoic acid derivatives as selective human β3-adrenergic receptor agonists

Abstract: Molecular modeling studies were performed to develop a predictive common pharmacophore hypothesis (CPH) and use it for alignment in threedimensional (3D) quantitative structure-activity relationship (QSAR) studies using CoMFA and CoMSIA, with a diverse set of 80 b 3 -adrenergic receptor (b 3 -AR) agonists. Using PHASE (Pharmacophore Alignment and Scoring Engine) six-point CPH with one acceptor, one negative charge, one positive charge, and three rings, features were derived for pharmacophore-based alignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…They were examined in SciFinder for potentially known agonist activities on the hβ 3 -AR prior to testing (the summary of search results is provided in Supporting Information Table S2). Pharmacophore features [a] Software Prathipati-Saxena model [27] 51 (34,17) RA, PI, HBD, HBA, H Catalyst v4.6 Shakya model [28] 4 HBA, HBD, HBA, HpAr, HpAl, RA Catalyst v4.7 Telvekar model [29] 80 (56,24) RA, HBA, PI, RA, RA, NI PHASE v3.0…”
Section: Pharmacophore Modeling and Virtual Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…They were examined in SciFinder for potentially known agonist activities on the hβ 3 -AR prior to testing (the summary of search results is provided in Supporting Information Table S2). Pharmacophore features [a] Software Prathipati-Saxena model [27] 51 (34,17) RA, PI, HBD, HBA, H Catalyst v4.6 Shakya model [28] 4 HBA, HBD, HBA, HpAr, HpAl, RA Catalyst v4.7 Telvekar model [29] 80 (56,24) RA, HBA, PI, RA, RA, NI PHASE v3.0…”
Section: Pharmacophore Modeling and Virtual Screeningmentioning
confidence: 99%
“…However, none of those studies involved experimental in vitro validation of predicted hits. [27][28][29][30][31] Therefore, this study aimed to perform pharmacophore-based virtual screening and also confirm the biological activity of selected hit compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, there have been only two reports of quantitative structure-activity relationship (QSAR) studies on selective compounds for the β3-AR [ 27 , 28 ], one of which was conducted by our research group [ 28 ]. In both cases, the studies were carried out on phenylethanolamine-type compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the 3D-QSAR techniques become useful as tools to rationally design and direct the synthesis of potentially active derivatives. Few QSAR studies on this receptor have been reported in the literature [ 28 , 29 , 30 ]. Some of the limitations presented by these works include low predictability of the test set compounds [ 28 ], poor data distribution along the line y = x, a narrow range of studied biological activity [ 29 ], and the low potency of compounds used in the formulation of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the limitations presented by these works include low predictability of the test set compounds [ 28 ], poor data distribution along the line y = x, a narrow range of studied biological activity [ 29 ], and the low potency of compounds used in the formulation of the model. Other studies do not demonstrate that the combination of the considered descriptors is optimal, which can lead to explanations of the structure–activity correlation based on nonsignificant information [ 30 ].…”
Section: Introductionmentioning
confidence: 99%